(untitled) - Rosen, Lawrence (Oxford, 2000)
One out of five people in the world today lives subject to Islamic law, but stereotypes of rigid doctrine or harsh punishment obscure an understanding of the values and style of reasoning that characterize everyday lslamic adjudication. By considering its larger social and cultural context, this book shows Islamic law to be a kind of common law system: justice is sought through a careful assessment of persons, more than facts, and justice resides not in equality but in a quest for equivalence.
Keywords: Islamic law,Sociological jurisprudence,Luật Đạo hồi,Luật xã hội học